Public elementary school principals as agents of change - Rico, Epifanio G., Jr. (Laoag City : [s.n.], 2014)
his study described the elementary school principals of the Division of Ilocos Norte who were identified as successful agents of change in their schools and communities. It described their characteristics and how they successfully implemented changes in their schools and work environments with regard to the following components of transformational leadership: intellectual stimulation, individualized consideration, inspirational motivation, and idealized influence. It likewise determined the stakeholders' impediments or enhancers to effect change and how they managed these.involvement and reactions to the changes effected by the principals, and identified the impediments or enchancers to effect change and how they managed these.
Bibliography: pages 107-109.
CHED-La Union
Keywords: Schools -- Administration